Patrimonial Education And Photography: he Clic@R Iitapina Project and the Rescue of The Local Memory - Malverdes, André; Gomes Barbosa, Anderson (Guará Journal, 2019)
It analyzes heritage education actions using photographs of person-al collections as artistic language to express the cultural manifesta-tions of a community, with the purpose of verifying their relationship with  the feeling  of  belonging  to  the  local  history  and  with the appreciation of their cultural patrimony. The approach of the problem occurred through quantitative research (statistical instruments) and qualitative,  using deduction as  a  research  method  to  evaluate  the  effectiveness of actions for society. It was found that the patrimonial education  workshop  presented  relevant  content  and that  its  prod-ucts  caused  positive socio-cultural impacts.  It  was  concluded  that  the patrimonial education methodology applied by the Clic@r Itapina project team was efficient for the purpose of awakening the sense of belonging and was a way to value the local culture. The hypoth-esis was also confirmed, because the more the access to the photo-graphs became available, the more affective feelings were aroused, bringing good memories. In the final analysis, it was verified that the information  content  of  the photographs  refers  to  the  feeling  of  belonging and to the appreciation of cultural heritage.
Keywords: Cultural heritage; Patrimonial education; Personal collections; Photography